Drawing in Space: Recording the Spatialised Feelings of Atmospheres - O'Toole, Kiera (BBDS - Black Book: Drawing and Sketching, 2025)
This presentation explores the notion of drawing as a means of recording the ‘spatialised feelings’ of everyday public spaces, aiming to enhance our awareness of pathically felt bodily experiences. Drawing upon the theory of new phenomenology, the research examines how the affective and expressive qualities of atmospheres, understood as corporeally felt impulses, influence the gestural drawing process. Focusing on sites in Ireland and Germany, the drawings, termed 'Affective Cartographies’, are records of the phenomenological experience of site’s atmosphere.Through this practice-based approach, the gestural line becomes a form of pathic knowing, revealing dimensions that are more felt than thought. This approach offers a deeper lived experience by encouraging us to sense ourselves pathically within our surroundings. The paper expands on how drawing, as an phenomenological act, can provide a meaningful account of what is usually perceived as 'in-situ', 'background' or 'environment.' By prioritising the felt body, this method of enquiry extends beyond the traditional five senses, offering a more holistic understanding of the spaces we inhabit and the act of drawing itself.